(untitled) (PANGEEA, 2025)
ABSTRACT: The Vâlcan Mount is formed on a Jurassic klippe limestone and present a particularly landscape in the Western Mountains. This paper presents assumptions geological genesis of the mountain and its importance in terms of tourism and economic. Mount is now an anthropogenic and geomorfological natural park. Here is the final workshop for the preparation of lime manufacturer by traditional methods, burnt lime kiln with wood. Key words: klippe; limestone; geological genesis; tourism; traditional methods.